An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Protective effect of adiponectin on paraquat-induced pulmonary fibrosis in mice - Rong Yao; Yarong He; Zhi Zeng; Zongan Liang; Yu Cao (Molecular & Cellular Toxicology, 2015)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Communities of gamasid mites on Eothenomys miletus in southwest China - Pei-Ying Peng; Xian-Guo Guo; Wen-Yu Song; Peng Hou; Yun-Ji Zou; Rong Fan; Xue-Song He (Biologia, 2015)